Management control systems and performance: evidence from Malaysian Local Authorities / Norazlina Ilias - Ilias, Norazlina (2016)
The purpose of this study was to investigate the structural relationship between organizational culture, management control systems (MCSs) and the performance of Malaysian local authorities. This study was motivated by the inconsistent findings concerning the relationship between the control system and performance that appeared in the current literature, as well as the personal observations of the researcher. Due to the inconsistencies in the findings, several studies suggest that future researchers investigate MCSs as a tool to improve the performance of organizations. Therefore, this study integrated the organizational culture and MCSs literature by investigating the control systems variable, as control systems have been widely discussed in management accounting literature as an important variable for the purpose of achieving organizational objectives. In this study, three dimensions of MCSs have been identified: external control, internal formal control, and internal informal control. The performance of the local authorities under study was measured using three dimensions of performance: financial, service quality, and procedural. A questionnaire-based survey was carried out to seek responses from 449 departments attached to the local authorities within Peninsular Malaysia. Out of the 449 questionnaires distributed, 367 were returned, which resulted in 335 usable responses that were used for further analysis. This study performed two phases of data analyses: preliminary analysis and structural equation modeling (SEM) analysis. The preliminary data analysis was performed using the statistical procedures of SPSS version 19.0, while SEM analysis was performed using AMOS 18.0. The findings of the study showed that the organizational culture significantly affects the internal formal control, internal informal control, financial performance, service quality performance, and procedural performance. The results also revealed that the external control and internal formal control were significantly associated with all three performance dimensions, as expected. However, the internal informal control only had a direct relationship with the service quality performance, and did not have a significant relationship with the financial performance and procedural performance. Additionally, external control was also found to be significantly related to the internal formal control. This study also reported that the external control, through the presence of the internal formal control, had a stronger relationship with the financial performance, service quality performance, and procedural performance, as compared to the direct relationship between the external control and performance. The relationships between organizational culture and service quality performance and procedural performance, through the internal formal control and the internal informal control were also reported to be significant. Therefore, this study supported the premise of the contingency theory, which holds that organizational culture can influence the practices of internal control systems, and, eventually affects the organizational performance. The results also generally support the hypothesis that internal formal control and internal informal control serve as important mediators in the relationship between organizational culture and performance, as well as between external control and performance.